2016
DOI: 10.12659/pjr.896475
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Computed Tomography Guided Percutaneous Radiofrequency Ablation Therapy for Osteoid Osteoma: Initial Results and Review of the Literature

Abstract: SummaryBackgroundThe aim of this retrospective study is to determine our experience of technique success rate, complications and clinical results in long term follow up for computed tomography (CT)-guided radiofrequency ablation [RA] therapy for osteoid osteoma (OO).Material/MethodsWe performed RA therapy to 18 patients with OO referred to interventional radiology from other clinics primarily from orthopedics; between January 2011 to May 2014. Daytime and nighttime pain intensity of 18 patients was noted accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…We observed that the mean nidus size was 8.12±1.52 mm. Similar results were seen in a study done by Karagoz et al, where the mean nidus size was 8.06 mm [25].…”
Section: Discussionsupporting
confidence: 91%
“…We observed that the mean nidus size was 8.12±1.52 mm. Similar results were seen in a study done by Karagoz et al, where the mean nidus size was 8.06 mm [25].…”
Section: Discussionsupporting
confidence: 91%
“…In the series of 86 cases by Nijland et al, skin burns were detected in 2 patients [15]. In the 18-case study by Karagoz et al, skin burns were detected in 1 patient [16]. We detected second-degree skin burns in 2 patients.…”
Section: Discussionmentioning
confidence: 56%
“…These findings are similar to the literature. [15,17] Compared with the available literature, the low number of cases, the absence of a control group, and the absence of histopathologic verifications may be considered as the weaknesses of our study. Although having no histopathologic verification in RFA treatment of OOs is seen as a disadvantage, Vanderschueren et al [8] have stated that they took samples for histopathologic examination before applying RF; however, such examination did not provide any histopathologic diagnosis in 62-64% of their patients.…”
Section: Discussionmentioning
confidence: 93%
“…There are various publications in the literature stating that the period for pain relief ranges between one to 15 days. [ 15 - 17 ] During the first evaluation on the 15th postoperative day, we examined the pain relief period in our patients and determined that it varies between two to eight days (average, 4.4 days). These findings are similar to the literature.…”
Section: Discussionmentioning
confidence: 99%